2018
DOI: 10.5935/0103-507x.20180067
|View full text |Cite
|
Sign up to set email alerts
|

The use of bedside echocardiography for measuring cardiac index and systemic vascular resistance in pediatric patients with septic shock

Abstract: ObjectiveFollow-up of cardiac index and systemic vascular resistance index by bedside echocardiography until resuscitation.MethodsA set of hemodynamic parameters was obtained, including cardiac output, stroke volume, cardiac index, systemic vascular resistance index, velocity time integral, myocardial performance index, capillary refill time, and heart rate at 0 hours after fluid boluses before the start of inotropes, and followed up after 6 hours and 24 hours.ResultsIncluded were 45 patients with community-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…More than half of the patients (58%) showed a low CO/high SVR state, and 22% had low CO and low vascular resistance (15). Abdalaziz et al studied 45 patients with community-acquired septic shock by bedside echocardiography and reported that 82% of their cases had the echocardiographic criteria of cold septic shock with low normal or low CI (≤ 3.3 L/m/m 2 ) and normal or high SVRI (≥ 1,600 dyn-sec/cm 5 /m 2 ), whereas the remaining had the echocardiographic criteria of warm septic shock (high CI > 6 L/m/m 2 ) with low normal or low SVRI (≤ 800 dyn-sec/cm 5 /m 2 ) (16). Hydration in the management of septic shock is a doubleedged sword; it can correct relative hypovolemia, which is due to capillary leakage, not taking enough fluids, and fluid losses and maintain organ flow (9); on the other hand, overhydration may cause pulmonary edema or increase mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the patients (58%) showed a low CO/high SVR state, and 22% had low CO and low vascular resistance (15). Abdalaziz et al studied 45 patients with community-acquired septic shock by bedside echocardiography and reported that 82% of their cases had the echocardiographic criteria of cold septic shock with low normal or low CI (≤ 3.3 L/m/m 2 ) and normal or high SVRI (≥ 1,600 dyn-sec/cm 5 /m 2 ), whereas the remaining had the echocardiographic criteria of warm septic shock (high CI > 6 L/m/m 2 ) with low normal or low SVRI (≤ 800 dyn-sec/cm 5 /m 2 ) (16). Hydration in the management of septic shock is a doubleedged sword; it can correct relative hypovolemia, which is due to capillary leakage, not taking enough fluids, and fluid losses and maintain organ flow (9); on the other hand, overhydration may cause pulmonary edema or increase mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…Infants and young children with septic shock often present with elevated systemic vascular resistance and low cardiac output in the context of myocardial dysfunction as part of a cold shock phenotype [24,25]. Biventricular dysfunction appears to be common.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Septic shock is the most common critical illness in intensive care unit (ICU), with long hospital stay, high cost, and high mortality ( 1 3 ). Intestinal perforation is one of the important causes of septic shock ( 4 , 5 ). Sepsis leads to complications in coagulation patients ( 6 ).…”
Section: Introductionmentioning
confidence: 99%